The problem with here is that it's where I'm from, by Jamie Kelly : Jim Benton's tales from Mackerel Middle School. - Benton, Jim. (New York : Scholastic, 2007)
Jamie Kelly shares with her diary her excitement about the fact that students from Wodehouse Middle School will be going to Mackerel Middle School temporarily.
G8
Keywords: Diaries -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories